Decision-making skills of high-performance youth soccer players: Validating a video-based diagnostic instrument with a soccer-specific motor response - Murr, D.; Larkin, P.; Höner, O. (German Journal of Exercise and Sport Research, 2021)
This study aimed to develop a valid video-based diagnostic instrument that assesses decision-making with a sport-specific motor response. Methods: A total of 86 German youth academy players (16.7± 0.9years) viewed game situations projected on a large video screen and were required to make a decision by dribbling and passing to one of three targets (representing different decision options). The test included 48 clips separated into two categories: build-up (bu) and offensive decisions (off). Criterion-related validity was tested based on age (i.e., U16, U17, and U19), playing status (i.e., minutes played in official matches of the current season) and in a prospective approach relating to future youth national team status (i.e., selected or nonselected). Finally, it was investigated whether decision-making competence was influenced by playing position (i.e., defenders vs. midfielders vs. forwards). Results: Instrumental reliability demonstrated satisfactory values for SCbu (r= 0.72), and lower for SCoff (r= 0.56). Results showed the diagnostic instrument is suitable for discriminating between playing status (SCbu: F= 0.22, p< 0.01; SCoff: F= 0.14, p< 0.05) and between younger (U16) and older players (U17> U16 in SCbu: F= 0.24 and SCoff: F= 0.39, p< 0.01; U19> U16 in SCbu: F= 0.41 and SCoff: F= 0.46, p< 0.01); however, there was no difference between U17 and U19 players. Furthermore, the predictive value of the test indicates that future youth national team players make better decisions with respect to the build-up category (SCbu: F= 0.20; p< 0.05), whereas playing position did not significantly influence decision-making competence. Conclusion: Results indicate the video-based decision-making diagnostic instrument can discriminate decision-making competence within a high-performance youth group. The outcomes associated with national youth team participation demonstrate the predictive value of the diagnostic instrument. This study provides initial evidence to suggest a new video-based diagnostic instrument with a soccer-specific motor response can be used within a talent identification process to assist with assessment of decision-making performance.